Effect of moderate hydrostatic pressures on the enzymatic activity and bioactive composition of pineapple by‐products. (17th September 2020) - Santos, Diana I.; Pinto, Carlos A.; Corrêa‐Filho, Luiz C.; Saraiva, Jorge A.; Vicente, António A.; Moldão‐Martins, Margarida
Abstract: The application of abiotic stresses by moderate hydrostatic pressures (MHP) is still underdeveloped. Abiotic stresses allow activating the enzymatic complexes inducing the synthesis of de novo bioactive compounds. Pineapple by‐products are rich in bromelain and bioactive compounds that can be enhanced through abiotic stresses. The aim of this study was to evaluate the effect of MHP on the enzymatic activity of pineapple by‐products. Pineapple by‐products were submitted to MHP (50–400 MPa between 1 and 15 min) according to a central composite factorial design matrix. Samples were stored at 5 ± 1°C for 24 hr, to allow enzymatic activity to occur. Enzymatic and antioxidant activities and total phenolic compounds (TPC) were quantified. MHP promoted a 262% increase in the phenylalanine ammonia‐lyase activity and 36% increase in TPC, in shell samples. In core the activity of bromelain increased 350%. These results pinpoint the potential to increase the value of pineapple by‐products by enhancing the amounts of bioactive compounds through MHP application. Practical application: Abiotic stresses can enhance enzyme activity, inducing the synthesis of bioactive compounds in living tissues. Hydrostatic pressure is an innovative nonthermal process that can be used to stabilize or increase enzymes' activity present in by‐products generated in the minimally processed fruit and vegetables industry. Moderate hydrostatic pressure (MHP) act as abiotic stress inducing de novo phenols synthesis and enhancing bromelain activity. After treatment, enriched material could be stabilized and then blended with foods and beverages to improve nutraceutical properties and help in the prevention and treatment of chronic diseases. The study demonstrates that MHP (150–250 MPa) applied to the pineapple core and pineapple shell produce a phenolic and bromelain rich product. Abstract :